Personality Variables and Human Resources Development in Nigeria - Nwankwo, Okechukwu Dominic; Akam .G. Uche (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2011)
This research analyzed the effects of personality variables on human resources development. Trait theory of personality and its influences on behavioural (personality) tendencies formed the conceptual background. Consequently, personal variables like intellectual abilities, and physical abilities, as well as social variables emerged as the major determinants of human resources development. In order to cope with the dynamism and diversity of most modern work demand, it is necessary to develop human resources towards coping with “temporariness” (flux of changes). A number of factors were identified as being relevant implications of effective human resources development. These were reduction in lay-off, skills improvements, and work adaptation. However, the problems militating against effective human resources development in Nigeria were poorly defined personnel development programme, lack of practice of acquired skills, incompetent trainers, lack of feedback, and non-utilization of experts like psychologists. Consequently, it is recommended that these problems could be solved by ensuring that individuals are trained to be adaptive to the inevitable changing work requirements. Again, human resources development programme should be objectively focused, so as to avoid it being converted into a holiday occasion.